Preparation method of breathable, antibacterial and self-cleaning TPU sports kneecap
By selective laser sintering, printing the hollow structure of TPU sports knee pads and applying antibacterial and self-cleaning coatings, the problems of heavy knee pads and poor breathability are solved, and high breathability, antibacterial and self-cleaning performance are improved, and sports are improved Knee pads comfort and hygiene.
Patent Information
- Application Number
- CN202411465604.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-03
AI Technical Summary
The existing exercise knee pads are thick and have poor breathability, which leads to accumulation of heat and bacterial growth during exercise, affecting comfort and hygiene.
The TPU sports knee pads with hollow structures were printed using selective laser sintering technology and coated with antibacterial, self-cleaning superhydrophobic modified GO-WPU emulsion on its surface, which was formed by nano-SiO2 and TiO2 deposition of modified GO and attached silver ion antibacterial agents. Micro/nanostructures to achieve superhydrophobic and self-cleaning properties.
It significantly improves the breathability, sweatability and comfort of knee pads, while reducing the cleaning frequency, enhancing antibacterial performance and durability, and avoiding the use of high-cost, low-surface energy materials and potential irritation problems.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of selective laser sintering and antibacterial superhydrophobicity, and specifically relates to a method for preparing a breathable, antibacterial and self-cleaning TPU sports knee pad, in particular to a method for preparing a breathable, antibacterial and self-cleaning TPU sports knee pad based on SLS printing. Background Art
[0002] With the improvement of economic level and the enhancement of health awareness, national fitness activities have gradually become popular. In this context, as one of the most important joints in human movement, the protection of the knee is particularly important. Because the knee has a delicate structure and bears most of the weight of the human body, it is easy to be injured during exercise. Wearing knee pads can provide additional support and cushioning for the knees, and can reduce the impact of external impact on the knees during high-intensity exercise or accidental collisions. Therefore, it has become a common measure to prevent knee injuries.
[0003] At present, sports knee pads on the market are mainly made of knitted or elastomeric materials, which are designed to enhance their ability to absorb impact energy and resist compression, which results in the products being generally thick and heavy. Although this heavy design improves the protective performance, it also limits the flexibility of athletes to a certain extent and increases the discomfort of wearing. In addition, since the knee pads are in close contact with the skin, if the knee pads do not have good ventilation and breathability, a large amount of heat and sweat will accumulate during exercise, which not only reduces the comfort of wearing, but may also cause skin problems. Furthermore, if the knee pads are not breathable, it is easy to breed bacteria under long-term humid and stuffy conditions. In order to keep the knee pads clean and hygienic, they need to be washed and dried after use, which brings a lot of inconvenience to the users.
[0004] To sum up, a sports knee pad with good breathability, antibacterial function and self-cleaning properties undoubtedly has important practical application value and realistic significance. Summary of the invention
[0005] In view of the problems of existing sports knee pads, such as being relatively thick, having poor air permeability and perspiration discharge, being easily contaminated and breeding bacteria when exposed to a hot and humid environment for a long time, the present invention proposes the following solutions.
[0006] The invention provides a method for preparing a breathable, antibacterial and self-cleaning TPU sports knee pad, which comprises coating an antibacterial and self-cleaning coating on the surface of a hollow TPU sports knee pad formed by selective laser sintering; the antibacterial and self-cleaning coating is obtained by curing an antibacterial and self-cleaning emulsion.
[0007] The preparation of the antibacterial, self-cleaning emulsion comprises the following steps:
[0008] Step (1.1): adding 5 to 10 parts by weight of calcium phosphate to 10 to 40 parts by weight of 0.1 mol / L silver nitrate solution, filtering, washing and drying after the reaction to obtain calcium phosphate with attached silver ion antibacterial agent;
[0009] Step (1.2): 5 to 10 parts by weight of graphene oxide (GO) are dispersed in a solution, 40 to 60 parts by weight of NH3·H2O and 15 to 25 parts by weight of tetraethyl orthosilicate are added, and the mixture is stirred to form a suspension, and the suspension is filtered, washed, and dried to obtain nano-SiO2 deposition-modified GO;
[0010] Step (1.3): 5 to 10 parts by weight of the nano-SiO2 deposited modified GO prepared in step (1.2) are dispersed in a solution, 40 to 60 parts by weight of NH3·H2O and 15 to 25 parts by weight of tetraethyl orthotitanate are added, and stirred to form a suspension, and the suspension is filtered, washed, and dried to obtain nano-SiO2 and nano-TiO2 deposited modified GO, i.e., superhydrophobic modified GO;
[0011] Step (1.4): polydimethylsiloxane (PDMS), polyisocyanate and catalyst are mixed under a protective gas atmosphere, and a polymerization reaction is carried out at a temperature of 60 to 80°C; a hydrophilic chain extender is then added to carry out a chain extension reaction; 1,4-butanediol (BDO) is then added to carry out a chain extension reaction; the super-hydrophobic modified GO prepared in step (1.3) is then added, and the reaction is continued at a temperature of 50 to 70°C; triethylamine (TEA) and acetone are then added, and the reaction is continued at a temperature of 30 to 40°C; deionized water is then added, stirred, and the acetone is removed by vacuum rotary evaporation to obtain a super-hydrophobic modified GO-polyurethane emulsion (super-hydrophobic modified GO-WPU emulsion);
[0012] Step (1.5): Mix the calcium phosphate with attached silver ion antibacterial agent obtained in step (1.1) with the superhydrophobic modified GO-WPU emulsion obtained in step (1.4) at a mass ratio of 1:(5-20) to obtain an antibacterial superhydrophobic modified GO-WPU emulsion.
[0013] Furthermore, the method for preparing the breathable, antibacterial, self-cleaning TPU sports knee pads further comprises the following steps:
[0014] Step (2.1): mechanically blending TPU powder, antioxidant, and antistatic agent to obtain a mixed powder, and printing a sports knee pad having a hollow structure by selective laser sintering (SLS) technology;
[0015] Step (2.2): cleaning and drying the sports knee pad obtained in step (2.1) to obtain a clean and dry sports knee pad;
[0016] Step (2.3): attaching the antibacterial superhydrophobic modified GO-WPU emulsion to the surface of the sports knee pad obtained in step (2.2);
[0017] Step (2.4): drying and curing the sports knee pads with the antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (2.3) at 60-90° C. to obtain a breathable, antibacterial, self-cleaning TPU sports knee pad.
[0018] As a further optimization scheme, the components used in step (1.4) include:
[0019] Polydimethylsiloxane, 20 to 40 parts by weight;
[0020] Polyisocyanate, 15 to 25 parts by mass;
[0021] Catalyst, 0.1-0.2 parts by mass;
[0022] Hydrophilic chain extender, 2 to 4 parts by weight;
[0023] 1,4-Butanediol, 1 to 2 parts by mass;
[0024] Superhydrophobic modified GO, 5 to 25 parts by mass;
[0025] Triethylamine, 2-4 parts;
[0026] Deionized water, 80-120 parts by weight;
[0027] Acetone: 30-50 parts by weight.
[0028] As a further optimization scheme, in step (1.4), the average molecular weight of polydimethylsiloxane is 1000-2000.
[0029] As a further optimization scheme, in step (1.4), the polyisocyanate is one or more of isophorone diisocyanate, hexamethylene diisocyanate, and toluene diisocyanate.
[0030] As a further optimization scheme, in step (1.4), the catalyst is an organic metal catalyst or a tertiary amine catalyst, wherein the organic metal catalyst is one or more of dibutyltin dilaurate, stannous octoate, and dibutyltin diacetate.
[0031] As a further optimization scheme, in step (1.4), the hydrophilic chain extender is one or more of 2,2-dihydroxymethylpropionic acid, dihydroxy half ester, and sodium ethylenediaminesulfonate.
[0032] As a further optimization scheme, in step (2.1), the sports knee pad has a three-dimensional mesh hollow structure, and the hollowness of the sports knee pad gradually increases from the outside to the inside; the mixed powder includes: TPU powder, 90 to 110 parts by mass; antioxidant, 0.5 to 1 part by mass; antistatic agent, 3 to 5 parts by mass.
[0033] As a further optimization scheme, the antioxidant is one or more of butylated hydroxytoluene (BHT) antioxidant, 1010 antioxidant, and AO-30 antioxidant; the antistatic agent is one or more of ethoxylated alkyl amines, ethoxylated alkyl acid amines, and ethoxylated lauryl amide.
[0034] As a further optimization scheme, in step (2.3), the sports knee pad obtained in step (2.2) is placed in a dipping box and fixed at the bottom of the box, and then the antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (1.5) is injected into the dipping box, the liquid level of the emulsion exceeds the sports knee pad by 1 to 3 cm, the dipping time is 60 to 120 seconds, and during the dipping period, the fixture of the sports knee pad is evenly rotated in the clockwise and counterclockwise directions for 3 to 5 times respectively. After the rotation is completed, the sports knee pad is lifted from the emulsion, immersed and repeated 1 to 3 times to obtain a sports knee pad with the antibacterial superhydrophobic modified GO-WPU emulsion attached to the surface.
[0035] Beneficial Effects
[0036] (1) The present invention adopts the selective laser sintering (SLS) technology to form sports knee pads. By designing and manufacturing a sports knee pad with a gradient hollow lattice structure with a gradually increasing hollow degree from the outside to the inside, it can not only significantly improve the performance of the sports knee pad in absorbing the energy generated by the impact, but also improve the ventilation, air permeability and perspiration of the sports knee pad, and also improve the lightness, softness and comfort of the sports knee pad. Selective laser sintering (SLS) is a kind of 3D printing technology. It uses computer-aided design and manufacturing, adopts the principle of layered manufacturing and superposition, and directly forms powder materials into three-dimensional solid parts. It is not limited by the complexity of the shape of the formed parts, does not require any molds, and can produce hollow structural parts that are difficult or even impossible to prepare by traditional injection molding, extrusion and other molding processes.
[0037] (2) The present invention grows nano-scale SiO2 and TiO2 on GO to obtain super-hydrophobic modified GO, and then synthesizes super-hydrophobic modified GO-WPU emulsion through emulsion polymerization. The super-hydrophobic modified GO-WPU emulsion is compounded with synthetic calcium phosphate with attached silver ion antibacterial agent, and then coated on a sports knee pad to prepare a sports knee pad with an antibacterial and self-cleaning coating.
[0038] (3) The present invention generates many micro-protrusions and nano-protrusions on the TPU sports knee pads, wherein the micro-protrusions are composed of GO and the nano-protrusions are composed of nano-SiO2 and TiO2, thereby constructing an ideal micro / nano structure to achieve super-hydrophobic and self-cleaning properties. The water contact angle on the surface of the product can reach about 160°, which can reduce the frequency of cleaning the knee pads. The microstructure constructed by this method has multi-scale protrusions, and the self-cleaning performance will not be significantly reduced due to the loss of single-scale protrusions. In addition, this method avoids coating the surface of the product with expensive low-surface energy materials, and also avoids the adverse effects of solvents such as hexadecyltrimethoxysilane used in the coating process of low-surface energy materials on the human body, such as respiratory irritation and skin contact irritation.
[0039] (4) The present invention adopts a coating process, which is almost unaffected by the structure and shape of the outer surface of the workpiece and has a low cost. Moreover, this method makes full use of the penetration and anchoring effect of the coating on the micro-voids on the surface of the SLS printed workpiece, so that the coating has a strong bonding strength, is not easy to fall off, and has stronger durability. DETAILED DESCRIPTION
[0040] The present invention is further illustrated by specific examples below. These examples are exemplary and are intended to illustrate the problem and explain the present invention, but are not intended to be limiting.
[0041] The calcium phosphate with attached silver ion antibacterial agent and superhydrophobic modified GO in the subsequent embodiments of the present invention are prepared by the following scheme.
[0042] Step 1: Add 10g calcium phosphate to 40g 0.1mol / L silver nitrate solution, and react for 1h at 25℃ and 100r / min. Filter, then wash with deionized water 2-3 times, and finally put into a 60℃ vacuum oven to dry for 8h to obtain calcium phosphate with silver ion antibacterial agent attached.
[0043] Step 2: Disperse 10g of graphene oxide (GO) in 200g of 90% ethanol aqueous solution, ultrasonically disperse for 60min, stir in a 30℃ water bath for 10min, then add 60g of NH3·H2O and 25g of tetraethyl orthosilicate in sequence, magnetically stir for 24h to obtain a suspension, filter, then wash with anhydrous ethanol 2 to 3 times, and finally put it in a 60℃ vacuum oven to dry for 8h to obtain nano-SiO2 deposition modified GO.
[0044] Step 3: Disperse 10g of GO sheets deposited with nano-SiO2 prepared in step 2 in 200g of 90% ethanol aqueous solution, ultrasonically disperse for 30min, stir in a 30°C water bath for 10min, then add 60g of NH3·H2O and 25g of tetraethyl orthotitanate in sequence, stir magnetically for 24h to obtain a suspension, filter, then wash with anhydrous ethanol 2 to 3 times, and finally dry in a 60°C vacuum oven for 8h to obtain nano-SiO2 and nano-TiO2 deposition modified GO, i.e., superhydrophobic modified GO.
[0045] Preparation of sports kneepads with hollow structures in subsequent embodiments of the present invention: Print sports kneepads with hollow lattice structures according to the printing model programmed by CAD. The hollow lattice is composed of a plurality of cells of a honeycomb structure, and the cells include a frame forming a closed polygon, a cell rib located in the frame, and a hollow cavity is formed between the frame and the cell rib. The cell size increases in a gradient from the outer layer to the inner layer, and the cell rod diameter decreases in a gradient from the outermost layer to the inner layer. The average thickness of the sports kneepad is 6 mm, and the hollowing rate is 75%.
[0046] Example 1
[0047] (1) Under N2 atmosphere, 30g polydimethylsiloxane (PDMS), 20g isophorone diisocyanate, and 0.1g dibutyltin dilaurate were reacted at a temperature of 80℃ and a stirring speed of 320r / min for 4h; then, 3g 2,2-dihydroxymethylpropionic acid was added and reacted under the same conditions for 4h; then 2g 1,4-butanediol (BDO) was added and reacted under the same conditions for 4h; then 15g of the prepared superhydrophobic modified GO was added and reacted at a temperature of 65℃ and a stirring speed of 320r / min for 1h; then, 2g triethylamine (TEA) was added and reacted at a temperature of 35℃ and a stirring speed of 320r / min for 30min; finally, 100g deionized water was added and reacted at a stirring speed of 1500r / min for 5min, and acetone was removed by decompression using a rotary evaporator at 40℃ to obtain a superhydrophobic modified GO-WPU emulsion.
[0048] (2) 5 g of calcium phosphate with attached silver ion antibacterial agent was mixed with 100 g of super hydrophobic modified GO-WPU emulsion obtained in step (1) to obtain antibacterial super hydrophobic modified GO-WPU emulsion.
[0049] (3) 2 kg of TPU powder, 20 g of BHT, and 100 g of ethoxylated alkylamine were mechanically blended for 2 h, and a sports knee brace with a hollow structure was printed using selective laser sintering (SLS) technology.
[0050] (4) The sports knee pads were rinsed with a 30% ethanol aqueous solution and soaked in the 30% ethanol aqueous solution for 30 minutes, and then placed in a 60° C. forced air oven for drying for 6 hours to obtain a clean and dry sports knee pad.
[0051] (5) The sports knee pad obtained in step (4) is placed in a dipping box and fixed at the bottom of the box, and then the antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (2) is slowly injected into the dipping box, and the liquid level of the emulsion exceeds the sports knee pad by 1 to 3 cm. The dipping time is 4 minutes. During the dipping period, the clamp of the sports knee pad is evenly rotated in the clockwise direction and the counterclockwise direction for 3 to 5 times. After the rotation is completed, the sports knee pad is lifted from the emulsion and immersed in the emulsion for 1 to 3 times to obtain a sports knee pad with the antibacterial superhydrophobic modified GO-WPU emulsion attached to the surface.
[0052] (6): The sports knee pad with antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (5) is dried at 60° C. for 6 hours to obtain the breathable, antibacterial, self-cleaning TPU sports knee pad.
[0053] Example 2
[0054] (1) Under N2 atmosphere, 30g polydimethylsiloxane (PDMS), 20g isophorone diisocyanate, and 0.1g dibutyltin dilaurate were reacted at a temperature of 80℃ and a stirring speed of 320r / min for 4h; then, 3g 2,2-dihydroxymethylpropionic acid was added and reacted under the same conditions for 4h; then 2g 1,4-butanediol (BDO) was added and reacted under the same conditions for 4h; then 15g of the prepared superhydrophobic modified GO was added and reacted at a temperature of 65℃ and a stirring speed of 320r / min for 1h; then, 2g triethylamine (TEA) was added and reacted at a temperature of 35℃ and a stirring speed of 320r / min for 30min; finally, 100g deionized water was added and reacted at a stirring speed of 1500r / min for 5min, and acetone was removed by decompression using a rotary evaporator at 40℃ to obtain a superhydrophobic modified GO-WPU emulsion.
[0055] (2) 10 g of calcium phosphate with attached silver ion antibacterial agent was mixed with 100 g of super hydrophobic modified GO-WPU emulsion obtained in step (1) to obtain antibacterial super hydrophobic modified GO-WPU emulsion.
[0056] (3) 2 kg of TPU powder, 20 g of BHT, and 100 g of ethoxylated alkylamine were mechanically blended for 2 h, and a sports knee brace with a hollow structure was printed using selective laser sintering (SLS) technology.
[0057] (4) The sports knee pads were rinsed with a 30% ethanol aqueous solution and soaked in the 30% ethanol aqueous solution for 30 minutes, and then placed in a 60° C. forced air oven for drying for 6 hours to obtain a clean and dry sports knee pad.
[0058] (5) The sports knee pad obtained in step (4) is placed in a dipping box and fixed at the bottom of the box, and then the antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (2) is slowly injected into the dipping box, and the liquid level of the emulsion exceeds the sports knee pad by 1 to 3 cm. The dipping time is 4 minutes. During the dipping period, the clamp of the sports knee pad is evenly rotated in the clockwise direction and the counterclockwise direction for 3 to 5 times. After the rotation is completed, the sports knee pad is lifted from the emulsion and immersed in the emulsion for 1 to 3 times to obtain a sports knee pad with the antibacterial superhydrophobic modified GO-WPU emulsion attached to the surface.
[0059] (6) Drying the sports knee pad with the antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (5) at 60° C. for 6 hours to obtain the breathable, antibacterial, self-cleaning TPU sports knee pad.
[0060] Example 3
[0061] (1) Under N2 atmosphere, 30g polydimethylsiloxane (PDMS), 20g isophorone diisocyanate, and 0.1g dibutyltin dilaurate were reacted at a temperature of 80℃ and a stirring speed of 320r / min for 4h; then, 3g 2,2-dihydroxymethylpropionic acid was added and reacted under the same conditions for 4h; then 2g 1,4-butanediol (BDO) was added and reacted under the same conditions for 4h; then 15g of the prepared superhydrophobic modified GO was added and reacted at a temperature of 65℃ and a stirring speed of 320r / min for 1h; then, 2g triethylamine (TEA) was added and reacted at a temperature of 35℃ and a stirring speed of 320r / min for 30min; finally, 100g deionized water was added and reacted at a stirring speed of 1500r / min for 5min, and acetone was removed by decompression using a rotary evaporator at 40℃ to obtain a superhydrophobic modified GO-WPU emulsion.
[0062] (2) 15 g of calcium phosphate with attached silver ion antibacterial agent was mixed with 100 g of super hydrophobic modified GO-WPU emulsion obtained in step (1) to obtain antibacterial super hydrophobic modified GO-WPU emulsion.
[0063] (3) 2 kg of TPU powder, 20 g of BHT, and 100 g of ethoxylated alkylamine were mechanically blended for 2 h, and a sports knee brace with a hollow structure was printed using selective laser sintering (SLS) technology.
[0064] (4) The sports knee pads were rinsed with a 30% ethanol aqueous solution and soaked in the 30% ethanol aqueous solution for 30 minutes, and then placed in a 60° C. forced air oven for drying for 6 hours to obtain a clean and dry sports knee pad.
[0065] (5) The sports knee pad obtained in step (4) is placed in a dipping box and fixed at the bottom of the box, and then the antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (2) is slowly injected into the dipping box, and the liquid level of the emulsion exceeds the sports knee pad by 1 to 3 cm. The dipping time is 4 minutes. During the dipping period, the clamp of the sports knee pad is evenly rotated in the clockwise direction and the counterclockwise direction for 3 to 5 times. After the rotation is completed, the sports knee pad is lifted from the emulsion and immersed in the emulsion for 1 to 3 times to obtain a sports knee pad with the antibacterial superhydrophobic modified GO-WPU emulsion attached to the surface.
[0066] (6) Drying the sports knee pad with the antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (5) at 60° C. for 6 hours to obtain the breathable, antibacterial, self-cleaning TPU sports knee pad.
[0067] Example 4
[0068] (1) Under N2 atmosphere, 30g polydimethylsiloxane (PDMS), 20g isophorone diisocyanate, and 0.1g dibutyltin dilaurate were reacted at a temperature of 80℃ and a stirring speed of 320r / min for 4h; then, 3g 2,2-dihydroxymethylpropionic acid was added and reacted under the same conditions for 4h; then 2g 1,4-butanediol (BDO) was added and reacted under the same conditions for 4h; then 15g of the prepared superhydrophobic modified GO was added and reacted at a temperature of 65℃ and a stirring speed of 320r / min for 1h; then, 2g triethylamine (TEA) was added and reacted at a temperature of 35℃ and a stirring speed of 320r / min for 30min; finally, 100g deionized water was added and reacted at a stirring speed of 1500r / min for 5min, and acetone was removed by decompression using a rotary evaporator at 40℃ to obtain a superhydrophobic modified GO-WPU emulsion.
[0069] (2) 20 g of calcium phosphate with attached silver ion antibacterial agent was mixed with 100 g of super hydrophobic modified GO-WPU emulsion obtained in step (1) to obtain antibacterial super hydrophobic modified GO-WPU emulsion.
[0070] (3) 2 kg of TPU powder, 20 g of BHT, and 100 g of ethoxylated alkylamine were mechanically blended for 2 h, and a sports knee brace with a hollow structure was printed using selective laser sintering (SLS) technology.
[0071] (4) The sports knee pads were rinsed with a 30% ethanol aqueous solution and soaked in the 30% ethanol aqueous solution for 30 minutes, and then placed in a 60° C. forced air oven for drying for 6 hours to obtain a clean and dry sports knee pad.
[0072] (5) The sports knee pad obtained in step (4) is placed in a dipping box and fixed at the bottom of the box, and then the antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (2) is slowly injected into the dipping box, and the liquid level of the emulsion exceeds the sports knee pad by 1 to 3 cm. The dipping time is 4 minutes. During the dipping period, the clamp of the sports knee pad is evenly rotated in the clockwise direction and the counterclockwise direction for 3 to 5 times. After the rotation is completed, the sports knee pad is lifted from the emulsion and immersed in the emulsion for 1 to 3 times to obtain a sports knee pad with the antibacterial superhydrophobic modified GO-WPU emulsion attached to the surface.
[0073] (6) Drying the sports knee pad with the antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (5) at 60° C. for 6 hours to obtain the breathable, antibacterial, self-cleaning TPU sports knee pad.
[0074] Example 5
[0075] (1) Under N2 atmosphere, 30g polydimethylsiloxane (PDMS), 20g isophorone diisocyanate, and 0.1g dibutyltin dilaurate were reacted at 80℃ and stirring speed of 320r / min for 4h; then, 3g 2,2-dihydroxymethylpropionic acid was added and reacted under the same conditions for 4h; then, 2g 1,4-butanediol (BDO) was added and reacted under the same conditions for 4h; then, 5g of the prepared superhydrophobic modified GO was added and reacted at 65℃ and stirring speed of 320r / min for 1h; then, 2g triethylamine (TEA) was added and reacted at 35℃ and stirring speed of 320r / min for 30min; finally, 100g deionized water was added and reacted at 1500r / min stirring speed for 5min, and acetone was removed by decompression at 40℃ using a rotary evaporator to obtain a superhydrophobic modified GO-WPU emulsion.
[0076] (2) 15 g of calcium phosphate with attached silver ion antibacterial agent was mixed with 100 g of super hydrophobic modified GO-WPU emulsion obtained in step (1) to obtain antibacterial super hydrophobic modified GO-WPU emulsion.
[0077] (3) 2 kg of TPU powder, 20 g of BHT, and 100 g of ethoxylated alkylamine were mechanically blended for 2 h, and a sports knee brace with a hollow structure was printed using selective laser sintering (SLS) technology.
[0078] (4) The sports knee pads were rinsed with a 30% ethanol aqueous solution and soaked in the 30% ethanol aqueous solution for 30 minutes, and then placed in a 60° C. forced air oven for drying for 6 hours to obtain a clean and dry sports knee pad.
[0079] (5) The sports knee pad obtained in step (4) is placed in a dipping box and fixed at the bottom of the box, and then the antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (2) is slowly injected into the dipping box, and the liquid level of the emulsion exceeds the sports knee pad by 1 to 3 cm. The dipping time is 4 minutes. During the dipping period, the clamp of the sports knee pad is evenly rotated in the clockwise direction and the counterclockwise direction for 3 to 5 times. After the rotation is completed, the sports knee pad is lifted from the emulsion and immersed in the emulsion for 1 to 3 times to obtain a sports knee pad with the antibacterial superhydrophobic modified GO-WPU emulsion attached to the surface.
[0080] (6) Drying the sports knee pad with the antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (5) at 60° C. for 6 hours to obtain the breathable, antibacterial, self-cleaning TPU sports knee pad.
[0081] Example 6
[0082] (1) Under N2 atmosphere, 30g polydimethylsiloxane (PDMS), 20g isophorone diisocyanate, and 0.1g dibutyltin dilaurate were reacted at a temperature of 80℃ and a stirring speed of 320r / min for 4h; then, 3g 2,2-dihydroxymethylpropionic acid was added and reacted under the same conditions for 4h; then 2g 1,4-butanediol (BDO) was added and reacted under the same conditions for 4h; then 10g of the prepared superhydrophobic modified GO was added and reacted at a temperature of 65℃ and a stirring speed of 320r / min for 1h; then, 2g triethylamine (TEA) was added and reacted at a temperature of 35℃ and a stirring speed of 320r / min for 30min; finally, 100g deionized water was added and reacted at a stirring speed of 1500r / min for 5min, and acetone was removed under reduced pressure using a rotary evaporator at 40℃ to obtain a superhydrophobic modified GO-WPU emulsion.
[0083] (2) 15 g of calcium phosphate with attached silver ion antibacterial agent was mixed with 100 g of super hydrophobic modified GO-WPU emulsion obtained in step (1) to obtain antibacterial super hydrophobic modified GO-WPU emulsion.
[0084] (3) 2 kg of TPU powder, 20 g of BHT, and 100 g of ethoxylated alkylamine were mechanically blended for 2 h, and a sports knee brace with a hollow structure was printed using selective laser sintering (SLS) technology.
[0085] (4) The sports knee pads were rinsed with a 30% ethanol aqueous solution and soaked in the 30% ethanol aqueous solution for 30 minutes, and then placed in a 60° C. forced air oven for drying for 6 hours to obtain a clean and dry sports knee pad.
[0086] (5) The sports knee pad obtained in step (4) is placed in a dipping box and fixed at the bottom of the box, and then the antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (2) is slowly injected into the dipping box, and the liquid level of the emulsion exceeds the sports knee pad by 1 to 3 cm. The dipping time is 4 minutes. During the dipping period, the clamp of the sports knee pad is evenly rotated in the clockwise direction and the counterclockwise direction for 3 to 5 times. After the rotation is completed, the sports knee pad is lifted from the emulsion and immersed in the emulsion for 1 to 3 times to obtain a sports knee pad with the antibacterial superhydrophobic modified GO-WPU emulsion attached to the surface.
[0087] (6) Drying the sports knee pad with the antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (5) at 60° C. for 6 hours to obtain the breathable, antibacterial, self-cleaning TPU sports knee pad.
[0088] Example 7
[0089] (1) Under N2 atmosphere, 30g polydimethylsiloxane (PDMS), 20g isophorone diisocyanate, and 0.1g dibutyltin dilaurate were reacted at a temperature of 80℃ and a stirring speed of 320r / min for 4h; then, 3g 2,2-dihydroxymethylpropionic acid was added and reacted under the same conditions for 4h; then 2g 1,4-butanediol (BDO) was added and reacted under the same conditions for 4h; then 20g of the prepared superhydrophobic modified GO was added and reacted at a temperature of 65℃ and a stirring speed of 320r / min for 1h; then, 2g triethylamine (TEA) was added and reacted at a temperature of 35℃ and a stirring speed of 320r / min for 30min; finally, 100g deionized water was added and reacted at a stirring speed of 1500r / min for 5min, and acetone was removed by decompression using a rotary evaporator at 40℃ to obtain a superhydrophobic modified GO-WPU emulsion.
[0090] (2) 15 g of calcium phosphate with attached silver ion antibacterial agent was mixed with 100 g of super hydrophobic modified GO-WPU emulsion obtained in step (1) to obtain antibacterial super hydrophobic modified GO-WPU emulsion.
[0091] (3) 2 kg of TPU powder, 20 g of BHT, and 100 g of ethoxylated alkylamine were mechanically blended for 2 h, and a sports knee brace with a hollow structure was printed using selective laser sintering (SLS) technology.
[0092] (4) The sports knee pads were rinsed with a 30% ethanol aqueous solution and soaked in the 30% ethanol aqueous solution for 30 minutes, and then placed in a 60° C. forced air oven for drying for 6 hours to obtain a clean and dry sports knee pad.
[0093] (5) The sports knee pad obtained in step (4) is placed in a dipping box and fixed at the bottom of the box, and then the antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (2) is slowly injected into the dipping box, and the liquid level of the emulsion exceeds the sports knee pad by 1 to 3 cm. The dipping time is 4 minutes. During the dipping period, the clamp of the sports knee pad is evenly rotated in the clockwise direction and the counterclockwise direction for 3 to 5 times. After the rotation is completed, the sports knee pad is lifted from the emulsion and immersed in the emulsion for 1 to 3 times to obtain a sports knee pad with the antibacterial superhydrophobic modified GO-WPU emulsion attached to the surface.
[0094] (6) Drying the sports knee pad with the antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (5) at 60° C. for 6 hours to obtain the breathable, antibacterial, self-cleaning TPU sports knee pad.
[0095] Example 8
[0096] (1) Under N2 atmosphere, 30g polydimethylsiloxane (PDMS), 20g isophorone diisocyanate, and 0.1g dibutyltin dilaurate were reacted at a temperature of 80℃ and a stirring speed of 320r / min for 4h; then, 3g 2,2-dihydroxymethylpropionic acid was added and reacted under the same conditions for 4h; then 2g 1,4-butanediol (BDO) was added and reacted under the same conditions for 4h; then 15g of the prepared superhydrophobic modified GO was added and reacted at a temperature of 65℃ and a stirring speed of 320r / min for 1h; then, 2g triethylamine (TEA) was added and reacted at a temperature of 35℃ and a stirring speed of 320r / min for 30min; finally, 100g deionized water was added and reacted at a stirring speed of 1500r / min for 5min, and acetone was removed by decompression using a rotary evaporator at 40℃ to obtain a superhydrophobic modified GO-WPU emulsion.
[0097] (2) 15 g of calcium phosphate with attached silver ion antibacterial agent was mixed with 100 g of super hydrophobic modified GO-WPU emulsion obtained in step (1) to obtain antibacterial super hydrophobic modified GO-WPU emulsion.
[0098] (3) 2 kg of TPU powder, 20 g of BHT, and 100 g of ethoxylated alkylamine were mechanically blended for 2 h, and a sports knee brace with a hollow structure was printed using selective laser sintering (SLS) technology.
[0099] (4) The sports knee pads were rinsed with a 30% ethanol aqueous solution and soaked in the 30% ethanol aqueous solution for 30 minutes, and then placed in a 60° C. forced air oven for drying for 6 hours to obtain a clean and dry sports knee pad.
[0100] (5) The sports knee pad obtained in step (4) is placed in a dipping box and fixed at the bottom of the box, and then the antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (2) is slowly injected into the dipping box, the liquid level of the emulsion exceeds the sports knee pad by 1 to 3 cm, the dipping time is 2 minutes, and during the dipping period, the fixture of the sports knee pad is uniformly rotated in the clockwise direction and the counterclockwise direction for 3 to 5 times respectively. After the rotation is completed, the sports knee pad is lifted out of the emulsion and immersed in the emulsion repeatedly for 1 to 3 times to obtain a sports knee pad with the antibacterial superhydrophobic modified GO-WPU emulsion attached to the surface.
[0101] (6) Drying the sports knee pad with the antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (5) at 60° C. for 6 hours to obtain the breathable, antibacterial, self-cleaning TPU sports knee pad.
[0102] Example 9
[0103] (1) Under N2 atmosphere, 30g polydimethylsiloxane (PDMS), 20g isophorone diisocyanate, and 0.1g dibutyltin dilaurate were reacted at a temperature of 80℃ and a stirring speed of 320r / min for 4h; then, 3g 2,2-dihydroxymethylpropionic acid was added and reacted under the same conditions for 4h; then 2g 1,4-butanediol (BDO) was added and reacted under the same conditions for 4h; then 15g of the prepared superhydrophobic modified GO was added and reacted at a temperature of 65℃ and a stirring speed of 320r / min for 1h; then, 2g triethylamine (TEA) was added and reacted at a temperature of 35℃ and a stirring speed of 320r / min for 30min; finally, 100g deionized water was added and reacted at a stirring speed of 1500r / min for 5min, and acetone was removed by decompression using a rotary evaporator at 40℃ to obtain a superhydrophobic modified GO-WPU emulsion.
[0104] (2) 15 g of calcium phosphate of silver ion antibacterial agent was mixed with 100 g of super hydrophobic modified GO-WPU emulsion obtained in step (1) to obtain antibacterial super hydrophobic modified GO-WPU emulsion.
[0105] (3) 2 kg of TPU powder, 20 g of BHT, and 100 g of ethoxylated alkylamine were mechanically blended for 2 h, and a sports knee brace with a hollow structure was printed using selective laser sintering (SLS) technology.
[0106] (4) The sports knee pads were rinsed with a 30% ethanol aqueous solution and soaked in the 30% ethanol aqueous solution for 30 minutes, and then placed in a 60° C. forced air oven for drying for 6 hours to obtain a clean and dry sports knee pad.
[0107] (5) The sports knee pad obtained in step (4) is placed in a dipping box and fixed at the bottom of the box, and then the antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (2) is slowly injected into the dipping box, and the liquid level of the emulsion exceeds the sports knee pad by 1 to 3 cm. The dipping time is 6 minutes. During the dipping period, the clamp of the sports knee pad is evenly rotated in the clockwise direction and the counterclockwise direction for 3 to 5 times. After the rotation is completed, the sports knee pad is lifted out of the emulsion and immersed in the emulsion for 1 to 3 times to obtain a sports knee pad with the antibacterial superhydrophobic modified GO-WPU emulsion attached to the surface.
[0108] (6) Drying the sports knee pad with the antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (5) at 60° C. for 6 hours to obtain the breathable, antibacterial, self-cleaning TPU sports knee pad.
[0109] Example 10
[0110] (1) Under N2 atmosphere, 30g polydimethylsiloxane (PDMS), 20g isophorone diisocyanate, and 0.1g dibutyltin dilaurate were reacted at a temperature of 80℃ and a stirring speed of 320r / min for 4h; then, 3g 2,2-dihydroxymethylpropionic acid was added and reacted under the same conditions for 4h; then 2g 1,4-butanediol (BDO) was added and reacted under the same conditions for 4h; then 15g of the prepared superhydrophobic modified GO was added and reacted at a temperature of 65℃ and a stirring speed of 320r / min for 1h; then, 2g triethylamine (TEA) was added and reacted at a temperature of 35℃ and a stirring speed of 320r / min for 30min; finally, 100g deionized water was added and reacted at a stirring speed of 1500r / min for 5min, and acetone was removed by decompression using a rotary evaporator at 40℃ to obtain a superhydrophobic modified GO-WPU emulsion.
[0111] (2) 15 g of calcium phosphate with attached silver ion antibacterial agent was mixed with 100 g of super hydrophobic modified GO-WPU emulsion obtained in step (1) to obtain antibacterial super hydrophobic modified GO-WPU emulsion.
[0112] (3) 2 kg of TPU powder, 20 g of BHT, and 100 g of ethoxylated alkylamine were mechanically blended for 2 h, and a sports knee brace with a hollow structure was printed using selective laser sintering (SLS) technology.
[0113] (4) The sports knee pads were rinsed with a 30% ethanol aqueous solution and soaked in the 30% ethanol aqueous solution for 30 minutes, and then placed in a 60° C. forced air oven for drying for 6 hours to obtain a clean and dry sports knee pad.
[0114] (5) The sports knee pad obtained in step (4) is placed in a dipping box and fixed at the bottom of the box, and then the antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (2) is slowly injected into the dipping box, and the liquid level of the emulsion exceeds the sports knee pad by 1 to 3 cm. The dipping time is 4 minutes. During the dipping period, the clamp of the sports knee pad is evenly rotated in the clockwise direction and the counterclockwise direction for 3 to 5 times. After the rotation is completed, the sports knee pad is lifted from the emulsion and immersed in the emulsion for 1 to 3 times to obtain a sports knee pad with the antibacterial superhydrophobic modified GO-WPU emulsion attached to the surface.
[0115] (6) Drying the sports knee pad with the antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (5) at 40° C. for 6 hours to obtain the breathable, antibacterial, self-cleaning TPU sports knee pad.
[0116] Embodiment 11
[0117] (1) Under N2 atmosphere, 30g polydimethylsiloxane (PDMS), 20g isophorone diisocyanate, and 0.1g dibutyltin dilaurate were reacted at a temperature of 80℃ and a stirring speed of 320r / min for 4h; then, 3g 2,2-dihydroxymethylpropionic acid was added and reacted under the same conditions for 4h; then 2g 1,4-butanediol (BDO) was added and reacted under the same conditions for 4h; then 15g of the prepared superhydrophobic modified GO was added and reacted at a temperature of 65℃ and a stirring speed of 320r / min for 1h; then, 2g triethylamine (TEA) was added and reacted at a temperature of 35℃ and a stirring speed of 320r / min for 30min; finally, 100g deionized water was added and reacted at a stirring speed of 1500r / min for 5min, and acetone was removed by decompression using a rotary evaporator at 40℃ to obtain a superhydrophobic modified GO-WPU emulsion.
[0118] (2) 15 g of calcium phosphate with attached silver ion antibacterial agent was mixed with 100 g of super hydrophobic modified GO-WPU emulsion obtained in step (1) to obtain antibacterial super hydrophobic modified GO-WPU emulsion.
[0119] (3) 2 kg of TPU powder, 20 g of BHT, and 100 g of ethoxylated alkylamine were mechanically blended for 2 h, and a sports knee brace with a hollow structure was printed using selective laser sintering (SLS) technology.
[0120] (4) The sports knee pads were rinsed with a 30% ethanol aqueous solution and soaked in the 30% ethanol aqueous solution for 30 minutes, and then placed in a 60° C. forced air oven for drying for 6 hours to obtain a clean and dry sports knee pad.
[0121] (5) The sports knee pad obtained in step (4) is placed in a dipping box and fixed at the bottom of the box, and then the antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (2) is slowly injected into the dipping box, and the liquid level of the emulsion exceeds the sports knee pad by 1 to 3 cm. The dipping time is 4 minutes. During the dipping period, the clamp of the sports knee pad is evenly rotated in the clockwise direction and the counterclockwise direction for 3 to 5 times. After the rotation is completed, the sports knee pad is lifted from the emulsion and immersed in the emulsion for 1 to 3 times to obtain a sports knee pad with the antibacterial superhydrophobic modified GO-WPU emulsion attached to the surface.
[0122] (6) Drying the sports knee pad with the antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (5) at 80° C. for 6 hours to obtain the breathable, antibacterial, self-cleaning TPU sports knee pad.
[0123] Comparative Example 1
[0124] The knee pad of this comparative example was not added with calcium phosphate with silver ion antibacterial agent during the preparation process.
[0125] (1) Under N2 atmosphere, 30g polydimethylsiloxane (PDMS), 20g isophorone diisocyanate, and 0.1g dibutyltin dilaurate were reacted at a temperature of 80℃ and a stirring speed of 320r / min for 4h; then, 3g 2,2-dihydroxymethylpropionic acid was added and reacted under the same conditions for 4h; then 2g 1,4-butanediol (BDO) was added and reacted under the same conditions for 4h; then 15g of the prepared superhydrophobic modified GO was added and reacted at a temperature of 65℃ and a stirring speed of 320r / min for 1h; then, 2g triethylamine (TEA) was added and reacted at a temperature of 35℃ and a stirring speed of 320r / min for 30min; finally, 100g deionized water was added and reacted at a stirring speed of 1500r / min for 5min, and acetone was removed by decompression using a rotary evaporator at 40℃ to obtain a superhydrophobic modified GO-WPU emulsion.
[0126] (2) 2 kg of TPU powder, 20 g of BHT, and 100 g of ethoxylated alkylamine were mechanically blended for 2 h, and a sports knee brace with a hollow structure was printed using selective laser sintering (SLS) technology.
[0127] (3) The sports knee pads were rinsed with a 30% ethanol aqueous solution and soaked in the 30% ethanol aqueous solution for 30 minutes, and then placed in a 60° C. forced air oven for drying for 6 hours to obtain a clean and dry sports knee pad.
[0128] (4) The sports knee pad obtained in step (4) is placed in a dipping box and fixed at the bottom of the box, and then the superhydrophobic modified GO-WPU emulsion obtained in step (1) is slowly injected into the dipping box, the liquid level of the emulsion exceeds the sports knee pad by 1 to 3 cm, the dipping time is 4 minutes, and during the dipping period, the fixture of the sports knee pad is uniformly rotated in the clockwise direction and the counterclockwise direction for 3 to 5 times respectively. After the rotation is completed, the sports knee pad is lifted out of the emulsion and immersed in the emulsion repeatedly for 1 to 3 times to obtain a sports knee pad with the superhydrophobic modified GO-WPU emulsion attached to the surface.
[0129] (5) Drying the sports knee pad with the superhydrophobic modified GO-WPU emulsion obtained in step (4) at 60° C. for 6 hours to obtain a knee pad.
[0130] Comparative Example 2
[0131] The knee pad of this comparative example was not prepared by adding superhydrophobic modified GO.
[0132] (1) Under N2 atmosphere, 30 g of polydimethylsiloxane (PDMS), 20 g of isophorone diisocyanate, and 0.1 g of dibutyltin dilaurate were reacted at a temperature of 80°C and a stirring speed of 320 r / min for 4 h; then, 3 g of 2,2-dihydroxymethylpropionic acid was added and reacted under the same conditions for 4 h; then, 2 g of 1,4-butanediol (BDO) was added and reacted under the same conditions for 4 h; then, 2 g of triethylamine (TEA) was added and reacted at a temperature of 35°C and a stirring speed of 320 r / min for 30 min; finally, 100 g of deionized water was added and reacted at a stirring speed of 1500 r / min for 5 min, and acetone was removed under reduced pressure using a rotary evaporator at 40°C to obtain a WPU emulsion.
[0133] (2) 15 g of calcium phosphate with attached silver ion antibacterial agent was mixed with 100 g of WPU emulsion obtained in step (1) to obtain an antibacterial WPU emulsion.
[0134] (3) 2 kg of TPU powder, 20 g of BHT, and 100 g of ethoxylated alkylamine were mechanically blended for 2 h, and a sports knee brace with a hollow structure was printed using selective laser sintering (SLS) technology.
[0135] (4) The sports knee pads were rinsed with a 30% ethanol aqueous solution and soaked in the 30% ethanol aqueous solution for 30 minutes, and then placed in a 60° C. forced air oven for drying for 6 hours to obtain a clean and dry sports knee pad.
[0136] (5) The sports knee pad obtained in step (4) is placed in a dipping box and fixed at the bottom of the box, and then the antibacterial WPU emulsion obtained in step (2) is slowly injected into the dipping box, the liquid level of the emulsion is 1 to 3 cm higher than the sports knee pad, and the dipping time is 4 minutes. During the dipping period, the clamp of the sports knee pad is evenly rotated in the clockwise direction and the counterclockwise direction for 3 to 5 times. After the rotation is completed, the sports knee pad is lifted out of the emulsion and immersed in the emulsion for 1 to 3 times to obtain a sports knee pad with the antibacterial WPU emulsion attached to the surface.
[0137] (6) Drying the sports knee pad with the antibacterial WPU emulsion obtained in step (5) at 80° C. for 6 hours to obtain a knee pad.
[0138] Effect verification
[0139] In order to fully understand the performance of the sports knee pads made of TPU in each embodiment and comparative example, water contact angle, antibacterial rate and air permeability tests were carried out respectively, wherein the water contact angle test was carried out in accordance with GB / T 30693-2014; the antibacterial rate test was carried out in accordance with GB / T 31402-2023; the air permeability test was carried out in accordance with GB / T5453-1997. The above test results are shown in Table 1.
[0140] Table 1 Performance test results
[0141] Example Water contact angle (°) Antibacterial rate (%) Air permeability (mm / s) Example 1 155 80 243 Example 2 159 87 257 Example 3 163 96 267 Example 4 158 97 252 Example 5 145 95 249 Example 6 156 97 262 Example 7 164 96 257 Example 8 156 93 257 Example 9 164 97 246 Example 10 160 93 252 Embodiment 11 162 97 261 Comparative Example 1 143 0 237 Comparative Example 2 126 95 222
[0142] The data in Table 1 show that the SLS-molded TPU sports kneepad has excellent air permeability. The antibacterial and self-cleaning properties of the synthesized coating are significantly affected by the calcium phosphate content of the attached silver ion antibacterial agent, the content of superhydrophobic modified GO, the immersion time and the curing temperature.
[0143] By analyzing the data in Table 1, it can be seen that by comparing Example 3 with Comparative Example 1, it is shown that the addition of calcium phosphate attached to the silver ion antibacterial agent can significantly improve the antibacterial properties of the product; with the increase in the content of calcium phosphate attached to the silver ion antibacterial agent (Examples 1, 2, 3, 4), the antibacterial rate of the TPU product increases, the antibacterial properties are improved, and the contact angle and air permeability of the product first increase and then decrease. The reason is that with the increase in the content of calcium phosphate attached to the silver ion antibacterial agent, the antibacterial properties of the product are improved, but with the increase in the content of calcium phosphate attached to the silver ion antibacterial agent, the inorganic components in the coating are excessive, and the density of the coating decreases, affecting the contact angle and air permeability of the product.
[0144] By analyzing the data in Table 1, it can be seen that by comparing Example 3 with Control Example 2, the introduction of superhydrophobic modified GO can significantly improve the hydrophobic properties of the product; as the content of superhydrophobic modified GO increases (Examples 5, 6, 3, 7), the water contact angle of the TPU product increases, and the self-cleaning performance improves. The reason is that as the content of superhydrophobic modified GO increases, the number of micron and nanometer-scale protrusions on the surface of the product increases, the roughness of the surface of the product increases, and the contact angle increases, thereby improving the self-cleaning performance of the product.
[0145] As the immersion time of the product in the emulsion increases (Examples 8, 3, 9), the water contact angle and antibacterial rate of the product increase, and the air permeability first increases and then decreases. Among them, when the immersion time of the product in the emulsion is 4 minutes, the product performance is the best. The reason is that as the immersion time of the product in the emulsion increases, the residual emulsion on the surface of the product increases, the coating thickness increases, and the performance of the product improves. If the immersion time is too long, the coating thickness will be too thick, affecting the air permeability of the coating. As the curing temperature of the product increases (Examples 10, 3, 11), the water contact angle, antibacterial rate, and air permeability of the product first increase and then slightly decrease. Among them, when the curing temperature is 60°C, the product performance is the best. The reason is that as the curing temperature increases, the cross-linking density of the coating increases and the performance improves, but when the temperature is too high, the chemical bond at the junction of the coating and the product is destroyed to a certain extent, which leads to a slight decrease in performance.
[0146] In summary, the present invention provides a breathable, antibacterial, self-cleaning TPU sports knee pad. The invention grows SiO2 and TiO2 on GO to obtain super-hydrophobic modified GO, and then coats the sports knee pad with an antibacterial and self-cleaning coating through an emulsion to prepare a breathable, antibacterial, self-cleaning TPU sports knee pad. On the one hand, by introducing an antibacterial agent, the product is endowed with antibacterial properties; on the other hand, by generating many micrometer-scale protrusions and nanometer-scale protrusions on the TPU sports knee pad through the coating, an ideal micro / nano structure is constructed to achieve super-hydrophobic properties. Therefore, the product has good self-cleaning and antibacterial properties.
[0147] In addition, due to the high flexibility of SLS molding, the above scheme can be used to manufacture sports kneepads with conventional structures, and can also conveniently manufacture sports kneepads with gradient hollow structures, shapes and structural parameters that are more suitable for different human bodies. The air circulation between the interior and the external environment of the sports kneepad with gradient hollow structures increases the breathability of the sports kneepad, helps sweat evaporate, reduces the feeling of stuffiness during exercise, and can significantly improve the user's comfort experience.
[0148] Of course, the present invention may also have a variety of embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the disclosure of the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a breathable, antibacterial, self-cleaning TPU sports kneepad, characterized in that: Coating antibacterial and self-cleaning coatings on the surface of hollow TPU sports knee pads formed by selective laser sintering; The antibacterial and self-cleaning coating is obtained by curing the antibacterial and self-cleaning emulsion; The preparation of the antibacterial and self-cleaning emulsion comprises the following steps: Step (1.1): adding 5 to 10 parts by weight of calcium phosphate to 10 to 40 parts by weight of a 0.1 mol / L silver nitrate solution, filtering, washing, and drying after the reaction to obtain calcium phosphate with attached silver ion antibacterial agent; Step (1.2): 5-10 parts by weight of graphene oxide (GO) are dispersed in a solution, 40-60 parts by weight of NH3·H2O and 15-25 parts by weight of tetraethyl orthosilicate are added, and the mixture is stirred to form a suspension, and the suspension is filtered, washed, and dried to obtain nano-SiO2 deposition-modified GO; Step (1.3): 5-10 parts by weight of the nano-SiO2 deposited modified GO prepared in step (1.2) are dispersed in a solution, 40-60 parts by weight of NH3·H2O and 15-25 parts by weight of tetraethyl orthotitanate are added, and stirred to form a suspension, and the suspension is filtered, washed, and dried to obtain nano-SiO2 and nano-TiO2 deposited modified GO, i.e., superhydrophobic modified GO; Step (1.4): polydimethylsiloxane (PDMS), polyisocyanate and catalyst are mixed under a protective gas atmosphere, and a polymerization reaction is carried out at a temperature of 60-80°C; a hydrophilic chain extender is then added to carry out a chain extension reaction; 1,4-butanediol (BDO) is then added to carry out a chain extension reaction; the super-hydrophobic modified GO prepared in step (1.3) is then added, and the reaction is continued at a temperature of 50-70°C; triethylamine (TEA) and acetone are then added, and the reaction is continued at a temperature of 30-40°C; deionized water is then added, stirred, and the acetone is removed by vacuum rotary evaporation to obtain a super-hydrophobic modified GO-polyurethane emulsion (super-hydrophobic modified GO-WPU emulsion); Step (1.5): The calcium phosphate with attached silver ion antibacterial agent obtained in step (1.1) is mixed with the superhydrophobic modified GO-WPU emulsion obtained in step (1.4) at a mass ratio of 1:(5-20) to obtain an antibacterial superhydrophobic modified GO-WPU emulsion.
2. The method for preparing the breathable, antibacterial, self-cleaning TPU sports kneepad according to claim 1, characterized in that: The following steps are also included: Step (2.1): mechanically blending TPU powder, antioxidant, and antistatic agent to obtain a mixed powder, and printing a sports knee pad having a hollow structure by selective laser sintering (SLS) technology; Step (2.2): cleaning and drying the sports knee pad obtained in step (2.1) to obtain a clean and dry sports knee pad; Step (2.3): attaching the antibacterial superhydrophobic modified GO-WPU emulsion to the surface of the sports knee pad obtained in step (2.2); Step (2.4): drying and curing the sports knee pad with the antibacterial superhydrophobic modified GO-WPU emulsion obtained in step (2.3) at 60-90° C. to obtain the breathable, antibacterial, self-cleaning TPU sports knee pad.
3. The method for preparing the breathable, antibacterial, self-cleaning TPU sports kneepad according to claim 2, characterized in that: The components used in step (1.4) include: Polydimethylsiloxane, 20-40 parts by mass; Polyisocyanate, 15-25 parts by mass; Catalyst, 0.1-0.2 parts by mass; Hydrophilic chain extender, 2-4 parts by weight; 1,4-Butanediol, 1-2 parts by mass; Superhydrophobic modified GO, 5-25 parts by mass; Triethylamine, 2-4 parts; Deionized water, 80-120 parts by weight; Acetone: 30-50 parts by mass.
4. The method for preparing the breathable, antibacterial, self-cleaning TPU sports kneepad according to claim 2, characterized in that: In the step (1.4), the average molecular weight of the polydimethylsiloxane is 1000-2000.
5. The method for preparing the breathable, antibacterial, self-cleaning TPU sports kneepad according to claim 2, characterized in that: In the step (1.4), the polyisocyanate is one or more of isophorone diisocyanate, hexamethylene diisocyanate, and toluene diisocyanate.
6. The method for preparing the breathable, antibacterial, self-cleaning TPU sports kneepad according to claim 2, characterized in that: In the step (1.4), the catalyst is an organic metal catalyst or a tertiary amine catalyst, wherein the organic metal catalyst is one or more of dibutyltin dilaurate, stannous octoate, and dibutyltin diacetate.
7. The method for preparing the breathable, antibacterial, self-cleaning TPU sports kneepad according to claim 2, characterized in that: In the step (1.4), the hydrophilic chain extender is one or more of 2,2-dihydroxymethylpropionic acid, dihydroxy half ester, and sodium ethylenediaminesulfonate.
8. The method for preparing the breathable, antibacterial, self-cleaning TPU sports kneepad according to claim 2, characterized in that: In the step (2.1), the sports knee pad has a three-dimensional mesh hollow structure, and the hollowness of the sports knee pad gradually increases from the outside to the inside; the mixed powder includes: TPU powder, 90-110 parts by mass; antioxidant, 0.5-1 parts by mass; antistatic agent, 3-5 parts by mass.
9. The method for preparing the breathable, antibacterial, self-cleaning TPU sports kneepad according to claim 8, characterized in that: The antioxidant is one or more of butylated hydroxytoluene (BHT) antioxidant, 1010 antioxidant, and AO-30 antioxidant; the antistatic agent is one or more of ethoxylated alkyl amine, ethoxylated alkyl acid amine, and ethoxylated lauryl amide.
10. The method for preparing the breathable, antibacterial, self-cleaning TPU sports kneepad according to claim 2, characterized in that: In the step (2.3), the sports knee pad obtained in the step (2.2) is placed in a dipping box and fixed to the bottom of the box, and then the antibacterial superhydrophobic modified GO-WPU emulsion obtained in the step (1.5) is injected into the dipping box, the liquid level of the emulsion exceeds the sports knee pad by 1-3 cm, the dipping time is 60-120 seconds, and during the dipping period, the fixture of the sports knee pad is uniformly rotated in the clockwise direction and the counterclockwise direction for 3-5 cycles respectively. After the rotation is completed, the sports knee pad is lifted from the emulsion, immersed and repeated 1-3 times to obtain a sports knee pad with the antibacterial superhydrophobic modified GO-WPU emulsion attached to the surface.
Citation Information
Cited By
Self-cleaning coating for post-treatment of 3D printed part and synthesis method
CN120944446A
High-performance composite fiber and breathable fabric made of high-performance composite fiber
CN121496604A